Patient-reported outcomes of symptom burden and quality of life in patients with polycythemia vera and essential thrombocythemia in Korea - Yoorin Cho (Medicine, 2026)
This cross-sectional survey aimed to identify factors affecting quality of life (QoL) in patients with polycythemia vera (PV) and essential thrombocythemia (ET). Participants comprised 189 patients with PV or ET receiving outpatient treatment in Seoul. Data were collected using a structured questionnaire and analyzed using linear multiple regression analysis. Factors affecting the QoL in patients with PV or ET, including overall QoL, functional scales, and symptom experience, were fatigue, disease duration, numbness/tingling, bone pain, fever, weight loss, abdominal discomfort, educational level, and female sex. Assessment of QoL and symptom burden in patients with PV and ET indicated that fatigue, disease duration, numbness/tingling, bone pain, fever, weight loss, abdominal discomfort, educational level, and female sex significantly influence QoL, highlighting the importance of active management and continuous monitoring of patient symptoms. Future research should evaluate the impact of comorbid conditions on symptom burden and QoL.